Instructional Design for Meaningful English Learning: Bridging Pedagogy, Technology, and Assessment - Dian Pariska; Rani Aulia Rayusda (Lembaga Yasin AlSys, 2026)
The integration of pedagogy, educational technology, and assessment has been extensively discussed in English language learning research; however, instructional design frameworks that systematically align these three components to support meaningful English language learning remain limited. This study aimed to develop an integrated instructional design framework that bridges pedagogical strategies, technology integration, and assessment practices in the context of English language learning. A conceptual qualitative approach was employed through an integrative literature review and systematic document analysis. The data sources comprised reputable journal articles, academic books, systematic reviews, and international policy documents published between 2010 and 2025, which were analyzed using thematic analysis. The results identified five main themes, namely learner-centered pedagogy, authentic learning activities, the functions of interactive technology, formative and authentic assessment, and integrated instructional design. The findings indicate that meaningful English language learning consistently emerges when learning objectives, learning activities, technology use, and assessment methods are coherently integrated within a structured instructional design. This study provides a theoretical contribution by positioning meaningful learning as an integrated instructional system and a practical contribution in the form of a framework to support lesson planning and curriculum development. The findings underscore the importance of coherence in instructional design for enhancing communicative competence, learning engagement, and the sustainability of English language learning outcomes.